Obraz Rosji w blogach literackich pisarzy rosyjskich: Image of Russia in literary blogs of Russian writers - Karwacka, Monika (Przegląd Wschodnioeuropejski, 2020)
The article is devoted to Russian writers who attempt to construct the image of contemporary Russia in the blogosphere. Blogs created by Prilepin, Griskhovets and Glukhovsky are analysed as a tool of creating the basis of modern national imaginary community. Literary blogs presented in cyberspace contribute to spreading the perception of Russia as an empire in the context of cultural and historical heritage. Aesthetic diversity and mental approach of the writers provides varied material to reconstruct the image of Russia. Although each of the bloggers has an individual idea of further development of their native country their presentations can be characterised by immanent features of Russian literary environment.